CIRCULAR ECONOMY IN ROMANIA: AN INDUSTRIAL SYNERGY IN THE AGRI-FOOD SECTOR - Dumitru Florin FRONE; Simona FRONE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
As a feature of the green economy, circular economy proposes the re-use of resources used in products whose shelf life has come to an end or which have lost their usefulness to construct new objects, the same quality or even better. The circular economy model may be the ideal solution for relaunching sustainably the European economy which has suffered in recent years (2008-2012). In the circular economy, the value of products, materials and resources is maintained in the economy for as long as possible and the generation of waste minimised. In this paper we shall stress on issues of eco-innovation promoting the circular economy in Romania. One of the most important concepts for the new paradigm of circular economy and resource efficiency improvements is the industrial symbiosis, implemented in eco-innovation parks (EInvP) developed to optimize economic and environmental efficiency of the involved companies and communities. In practice using industrial synergy as an approach to commercial operations – using, recovering and redirecting resources for reuse – means resources remain in productive use in the economy for longer. We analyse here a successful good practice of industrial synergy in the agri-food sector implemented within the ECOREG EInvP of Suceava County. The conclusions point to the important economic, social and environmental benefits to raise awareness for regional eco-innovation and circular economy prospects in Romania.